Vocal Attractiveness Matters: Social Preferences in Cooperative Behavior - Shang, Junchen; Liu, Zhihui (Frontiers in Psychology, 2022)
Research has shown the phenomenon that "what sounds beautiful is good" stereotype. It is not clear whether vocal attractiveness affects social decision-making in economic games. Here we investigated the neural mechanism of the influence of vocal attractiveness on cooperative decision- making, using a modified trust game task. Participants first heard a voice (attractive or unattractive) of the partner. They had enough time to decide whether to cooperate with the partner for a chance to earn monetary rewards. The behavioral results showed that participants made more invest choices in the attractive partner condition, and they were more likely to cooperate with the female partners in the unattractive voices condition. The ERP analysis for voice stimuli showed that attractive voices induced larger N1 amplitude than unattractive voices only in male voices condition. And female voices elicited smaller N1 and larger P2 amplitudes than male voices in both the attractive and unattractive voices condition. Larger P3 amplitude was evoked by female voices and attractive voices. In addition, a more positive LPC was induced by male voices and attractive voices. The present study suggested that attractive voices facilitated cooperative behavior, providing evidence for the "beauty premium" effect of the attractive voice. Moreover, participants were more likely to cooperate with female partners. In the early stage, gender information and male vocal attractiveness were processed automatically, suggesting that male vocal attractiveness was preferentially processed than female voice. In the late stage, participants allocated attention to both male and female vocal attractiveness.